On-Chip Nanoscale Plasmonic Optical Modulators - Abdelhamid, Abdalrahman Mohamed Nader (AUC Knowledge Fountain, 2021)
In this thesis work, techniques for downsizing Optical modulators to nanoscale for the purpose of utilization in on chip communication and sensing applications are explored. Nanoscale optical interconnects can solve the electronics speed limiting transmission lines, in addition to decrease the electronic chips heat dissipation. A major obstacle in the path of achieving this goal is to build optical modulators, which transforms data from the electrical form to the optical form, in a size comparable to the size of the electronics components, while also having low insertion loss, high extinction ratio and bandwidth. Also, lap-on-chip applications used for fast diagnostics, and which is based on photonic sensors and photonic circuitry, is in need for similar modulator specifications, while it loosens the spec on the modulator’s size. Silicon photonics is the most convenient photonics technology available for optical interconnects application, owing to its compatibility with the mature and cheap CMOS manufacturing process. Hence, building modulators which is exclusively compatible with this technology is a must, although, Plasmonics could be the right technology for downsizing the optical components, owing to its capability in squeezing light in subwavelength dimensions. Hence, our major goal is to build plasmonic modulators, that can be coupled directly to silicon waveguides. A Plasmonic Mach-Zehnder modulator was built, based on the orthogonal junction coupling technique. The footprint of the modulator is decreased to 0.6 4.7, extinction ratio of 15.8 dB and insertion loss of 3.38 dB at 10 volts was achieved in the 3D simulations. The voltage length product for the modulator is 47 V. The orthogonal junction coupler technique minimized the modulator’s footprint. On the other hand, photonic sensors favorably work in the mid-infrared region, owing to the presence of a lot of molecules absorption peaks in this region. Hence, III-V semiconductor media is used for this type of applications, owing to the availability of laser sources built of III-V media, and to the lower losses that these materials have in mid-infrared region. Hybrid plasmonic waveguide, formed of doped InAs, AlAs and GaAs is studied extensively. Based on this waveguide an electro-absorption modulator is built. The device showed an extinction ratio of 27 dB at 40 length, and 1.2 dB of insertion loss. The small device footprint predicts a much lower energy consumption.